2004
DOI: 10.1007/s00445-003-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic constraints on magma chambers at Hekla and Torfaj�kull volcanoes, Iceland

Abstract: Hekla and Torfajökull are active volcanoes at a rift-transform junction in south Iceland. Despite their location next to each other they are physically and geologically very different. Hekla is an elongate stratovolcano, built mainly of basaltic andesite. Torfajökull is a prominent rhyolitic centre with a 12-km-diameter caldera and extensive geothermal activity. The scope of this study is to examine the propagation of body waves of local earthquakes across the Hekla-Torfajökull area and look for volumes of ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 34 publications
5
48
3
Order By: Relevance
“…Although the degassing-related origin of the tremor is shallow, the resulting vibration can occur in a long channel and produce the characteristic low frequencies. Lack of evidence for a considerable Hekla magma chamber at the uppermost 14 km (Soosalu and Einarsson 2004) may give an estimate for the length of the eruptive conduit of Hekla.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the degassing-related origin of the tremor is shallow, the resulting vibration can occur in a long channel and produce the characteristic low frequencies. Lack of evidence for a considerable Hekla magma chamber at the uppermost 14 km (Soosalu and Einarsson 2004) may give an estimate for the length of the eruptive conduit of Hekla.…”
Section: Discussionmentioning
confidence: 97%
“…No propagating front of seismicity from depth towards the surface could be detected. We have studied the location of the magma chamber of Hekla (Soosalu and Einarsson 2004) and concluded that no seismic indicators of a prominent magma chamber at Hekla can be found in the uppermost 14 km.…”
Section: Discussionmentioning
confidence: 99%
“…Several early ground deformation studies inferred the magma reservoir depth at 5-10 km (Kjartansson and Gronvold, 1983;Sigmundsson et al, 1992), while a more recent and more encompassing work by Sturkell et al (2013) locate it closer to 10 km. However, other research has indicated that there is no significant molten material shallower than 14 km (Soosalu and Einarsson, 2004); and that the main storage chamber is located at 16 ± 2 km depth (Ofeigsson et al, 2011), or possibly as deep as 24 km (Geirsson et al, 2012). Petrological analysis provides evidence in support of magma storage at $9 km (Moune et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Hekla volcano (63.98°N 19.70°W) is one of the most frequently active, yet also one of the most unpredictable volcanoes in Europe, as a precursory seismic swarm has preceded its most recent eruptions by only a couple of hours or less (Soosalu and Einarsson, 2004 with the most recent one in 1104 AD (Thorarinsson, 1967;Larsen et al, 1999). Following this event and until 1947 CE Hekla continued to erupt 1-2 times per century with volumes up to 0.4 km 3 (Thorarinsson, 1950(Thorarinsson, , 1967Larsen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term changes were recorded 23-79 min before the outbreak of the eruptions. This short precursor time appears to be inconsistent with the large depth of 15-20 km to the feeding magma reservoir (Soosalu and Einarsson, 2004;Ofeigsson et al, 2011;Geirsson et al, 2012). Sturkell et al (2013) discuss this in connection with their finding that the surface eruptive fissure only extends to shallow levels in the crust, below which a pipe-like conduit extends downwards to the reservoir.…”
Section: Heklamentioning
confidence: 88%